TMEM100 Modulates TGF-β Signaling Pathway to Inhibit Colorectal Cancer Progression - Huixia Li; Chuan Cheng; Weibo You; Jiujian Zheng; Jie Xu; Peng Gao; Jianping Wang (Gastroenterology Research and Practice)
Objectives. This study investigated the functional mechanism of transmembrane protein 100 (TMEM100) as a tumor inhibitor gene in CRC cells and offered a reference for the treatment of CRC. Methods. The mRNA expression data of CRC were acquired from the TCGA database to mine differentially expressed mRNAs. The role of TMEM100 in the progression of CRC cells was evaluated by MTT, colony formation, scratch healing, and Transwell assays. The influence of TMEM100 on the TGF-β signaling pathway was detected by western blot. Results. TMEM100 was markedly lowly expressed in CRC. CRC cell growth was significantly suppressed by overexpressing TMEM100 but noticeably facilitated by silencing TMEM100. Overexpression of TMEM100 inhibited the activation of the TGF-β signaling pathway, thus inhibiting malignant progression of CRC. Conclusion. TMEM100 is lowly expressed in CRC, which can suppress CRC cell growth by regulating the TGF-β signaling pathway.